Developing “MEMANNAH” Digital Site on Prophet Muhammad and Medina’s Economy for Grade 5 PAI Learning - Mahmudah, Dwi Risa; Rizka, Fasya Nabila; Rachmat, Tia Destriana; Aeni, Ani Nur (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Religious Education in elementary schools has a very important role in developing the character and morals of students since the beginning of human history. This research uses the Design and Development (D&D) method which aims to develop and test the effectiveness of a technology-based product. The product developed is a Google Sites-based digital site,